A model 450 million years in the making: zebrafish and vertebrate immunity - Stephen A. Renshaw; Nikolaus S. Trede (The Company of Biologists, 2012)
Since its first splash 30 years ago, the use of the zebrafish model has been extended from a tool for genetic dissection of early vertebrate development to the functional interrogation of organogenesis and disease processes such as infection and cancer. In particular, there is recent and growing attention in the scientific community directed at the immune systems of zebrafish. This development is based on the ability to image cell movements and organogenesis in an entire vertebrate organism, complemented by increasing recognition that zebrafish and vertebrate immunity have many aspects in common. Here, we review zebrafish immunity with a particular focus on recent studies that exploit the unique genetic and in vivo imaging advantages available for this organism. These unique advantages are driving forward our study of vertebrate immunity in general, with important consequences for the understanding of mammalian immune function and its role in disease pathogenesis.